Virtual reality opens new frontiers in psychiatric treatment and education - Holmén Joel (Psykiatrian Tutkimussäätiö, 2025)
Virtual reality has been around the corner for quite some time. However, the technical development of the last few years has really brought affordable and easily usable virtual reality headsets to the larger public. Most studies on the use of virtual reality in psychiatry have focused on virtual reality exposure therapy, a form of exposure therapy using virtual reality to create environments which provoke anxiety. This has also been combined with elements of cognitive therapy. There are promising studies in using virtual reality to treat depression and psychotic delusions. Creating environments to represent the experiences of patients may also offer good ways of psychoeducation for parents, service providers and public alike